Operational Elements and Website Promotion Strategy of 10 Best Islamic High Schools in Indonesia: A Descriptive Analysis - Harida, Ratri; Eko Sujianto, Agus; Masrokan Muntohar, Prim (STAI Terpadu Yogyakarta, 2024)
School principals need to be aware of the competitive sector of madrasah marketing management, which includes the usage of websites. Using advertising strategies and operational components on madrasah websites might be an intelligent strategy to get an advantage in the educational field. The MA websites are to be described in this descriptive qualitative study based on their operational elements and promotional strategy. It also seeks to determine whether the features on the school website aligned with its primary objective of promoting marketing and information about the madrasa. Based on the findings, the order of the percentage of the presence of elements on each school website is as follows: elements for operational purposes (100%), elements for promotional purposes (85%), elements for non-operational and promotional purposes (83%), and elements that serve both operational and promotional purposes (78%). It can be concluded that the features on the 10 MAN website align with its main objective of facilitating information and marketing for the madras.